Novel conductive polymer composites based on CNTs/CNFs bridged liquid metal. (9th December 2020) - Pan, Xudong; Guo, Dengji; He, Hu
Abstract: Conductive polymer composites (CPCs) are vital and indispensable for the emerging field of soft electronics. In this work, a new strategy for using carbon nanotubes (CNTs)/carbon nanofibers (CNFs) and liquid metal droplets as multiphase hybrid fillers for CPCs is presented. We found that CPCs with multiphase hybrid conductive fillers had advantages in electromechanical properties over those with single solid-phase conductive fillers. CNTs/CNFs can easily form conductive paths in the polymer due to their excellent electrical conductivity with large aspect ratio. Self-repair of conductive networks was realized since the exposed Galinstan under strains could bridge the gap between CNTs/CNFs to form new conductive pathways. In addition, the influences of the size and content of conductive fillers on the electromechanical properties of CPCs were investigated. We found CPCs with liquid metals can be served as a flexible strain sensor under mild strain, while as a conductor under large strain due to the robust stability of resistance, which has not been reported yet in the literature. The CPCs presented in this work could provide potential applications in wearable electronics and flexible electronics.